The Effect of Financial Literacy, Financial Attitudes, and Financial Inclusion on the Financial Performance of MSMEs Tanete Riattang Bone Regency - Mega Utami; Sri Astuti Mualimin; Mahfudnurnajamuddin; Budiandriani (SEAN Institute, 2026)
This study aims to examine the influence of financial literacy, financial attitudes, and financial inclusion on the financial performance of MSMEs in Tanete Riattang District, Bone Regency.The population in this study includes all Micro, Small, and Medium Enterprises (MSMEs) actors in Tanete Riattang District, Bone Regency, with a total of 1,958 MSME actors. In determining the sample, the researcher used the Slovin formula so that as many as 100 respondents were obtained by simple random sampling technique. This study uses a quantitative approach with a survey method. The data used is primary data obtained through the distribution of a questionnaire with a Likert scale to the respondents. The data analysis method used was multiple linear regression analysis with the help of the SPSS program. The results of the study show that: 1) Financial literacy has a positive and significant effect on the financial performance of MSMEs, 2) Financial attitudes have a positive and significant effect on the financial performance of MSMEs, and 3) Financial inclusion has a positive and significant effect on the financial performance of MSMEs. In addition, simultaneously financial literacy, financial attitudes, and financial inclusion have a significant effect on the financial performance of MSMEs in Tanete Riattang District, Bone Regency.